Three-Dimensional Gastrointestinal Organoid Culture in Combination with Nerves or Fibroblasts: A Method to Characterize the Gastrointestinal Stem Cell Niche. (30th November 2015) - Pastuła, Agnieszka; Middelhoff, Moritz; Brandtner, Anna; Tobiasch, Moritz; Höhl, Bettina; Nuber, Andreas H.; Demir, Ihsan Ekin; Neupert, Steffi; Kollmann, Patrick; Mazzuoli-Weber, Gemma; Quante, Michael
Abstract : The gastrointestinal epithelium is characterized by a high turnover of cells and intestinal stem cells predominantly reside at the bottom of crypts and their progeny serve to maintain normal intestinal homeostasis. Accumulating evidence demonstrates the pivotal role of a niche surrounding intestinal stem cells in crypts, which consists of cellular and soluble components and creates an environment constantly influencing the fate of stem cells. Here we describe different 3D culture systems to culture gastrointestinal epithelium that should enable us to study the stem cell niche in vitro in the future: organoid culture and multilayered systems such as organotypic cell culture and culture of intestinal tissue fragments ex vivo . These methods mimic the in vivo situation in vitro by creating 3D culture conditions that reflect the physiological situation of intestinal crypts. Modifications of the composition of the culture media as well as coculturing epithelial organoids with previously described cellular components such as myofibroblasts, collagen, and neurons show the impact of the methods applied to investigate niche interactions in vitro . We further present a novel method to isolate labeled nerves from the enteric nervous system using Dclk1-CreGFP mice.